Existential counselling and psychotherapy - Langdridge, Darren; Sage eBooks (Los Angeles : SAGE, 2013)
This comprehensive introduction to existential therapy makes a difficult subject accessible, providing a comprehensive survey of past and contemporary ideas, philosophers and research. Later chapters explore cross-cutting contemporary issues in current existential counselling theory and practice and consider the future of the approach.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Existential psychotherapy; Counseling; Electronic books